Peran Celebrity Endorser Dalam Buying Decision (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2018)
The purpose of this study was to determine the role of celebrity endorsers on buying decisions. Using purposive sampling technique with 70 respondents which obtained from distributing questionnaires to buyers at PT. Timbul Jaya Motor Boyolali. Based on the multiple linear regression analysis method, either partially or jointly, it shows that the variables of attractiveness, credibility, and expertise of the celebrity endorser studied have a significant effect on buying decision. The Adjusted R-Square value is 0.670, which means that 67% of the buying decision variables can be explained by the attractiveness, credibility, and expertise of celebrity endorsers, while the remaining 33% is explained by other variables that not examined in this study.